Adoption Of Social Media-Based Political Campaigns Among Political Aspirants for The Local Government Chairmanship Elections In Oyo State - Adebayo , `John James; Bolanle, Morenike Adeoluwa; Olaimolu, Olaolu Olaruku (Corpus Intellectual, 2025)
The intensive use of social media for social activities establishes its indispensability in the political terrains. The wide adoption of social media for political and electioneering campaigns confirms new perspectives about the social and political functions of the mass media. Consequently, the paper is designed to investigate the use social media for political campaigns by Political aspirants for the Local Government Chairmanship election in Oyo State. A mixed-method was adopted to guide the study. Descriptive survey method and in-depth were used to guide the study. Descriptive survey method enables the researcher to access the opinions, attitudes, and thinking of the respondents that are very large. In-depth interview enables the researchers to have access to a few respondents who have detailed knowledge and informed views on subject matters under investigation. Findings showed that political aspirants who use the social media to campaign on social media only post pictures because it breaks illiteracy barriers among educated and the uneducated. Findings also showed that surging population of youths who are the main users of social media and major voters in an election has forced many politicians to register their presence on social media. Therefore, it is recommended that a unit must be established in any political party organisation to oversee social media activities of their political party candidates. As the users of social media keep increasing every day, there must be a course in secondary schools in Oyo State, and by extension Nigeria, to train the youths on informed and proper use of social media not only to benefit users but also to use the medium to bring about good governance and accountable leadership in Oyo State and Nigeria.